Promoting Critical Thinking Skills among Students in KSSR classroom - Wirawani Kamarulzaman (2018)
Students need to be equipped with critical thinking skills as they are the 21st century skills that will help students to face challenges in life ahead. Teachers themselves should be first to be equipped with the skills before they could teach students